The Effect of Adding Sodium-Potassium and Calcium-Magnesium to The Diet of Native Chicken Hen on Sex Ratio of Native Chicks - Saleh, DM; Iriyanti, N (ANIMAL PRODUCTION, 2010)
Thirtysix native hens were used to determine the effect of adding Sodium-Potassium and Calcium-Magnesium to the diet of Native Chicken hens on determination of native chick sexes. Fifteen hens (n=5; control, Na-K and Ca-Mg) were fed for 1 month and the other hens (n=6, for control, Na-K and Ca-Mg) were fed for two months, then  all hens were artificially inseminated, intra-vaginally, dose of 100 million perm cell per 0.1 ml, once a week for two weeks. On day 2 of insemination, all eggs were collected and evaluated daily for 14 days.  Every 5 days, the selected eggs were incubated for 7 days and followed by candling to assess fertility.  On day 21-22 of incubation, day old chicks were evaluated using vent sexing method to assess the sex ratio. Type of nutrition, fed at both for 1 month and two months had a similar results in fertility, hatchability and chick sex ratio:  62.79, 58.03, 59.52;  52.02, 50.93, 55.54 and 46.11, 51.89, 46.67 percent, respectively.  Feeding period of three type of diet value for fertility, hatchability and sex ratio is 59.19, 61.04; 53.61, 52.05, and 48.24, 47.86, respectively.  Our results suggest that different amount of ions in the diet of hens could not have a significant effect on the percent fertility, hatchability and sex ratio of chicks. (Animal Production 12(1): 12-15 (2010)Key Words : Na-K, Ca-Mg, fertility, hatchability, sex ratio, chicks